Intervention of the physical education professionals in public health before the SUS (Research, Society and Development, 2024)
In order to expand health actions, the Health Reform Movement and the creation of the Unified Health System - SUS became a right of all and a duty of the State, which aimed to promote the healthy life of Brazilian citizens. Objective: to analyze the insertion of the Physical Education professional in the SUS, reinforcing body practices and physical activity as a priority action in the area of public health. Methodology: this is a Narrative Review of Literature with a descriptive approach and qualitative nature. Results: demonstrated the systematization of 15 articles and 5 methodology books, published between the years 2019 and 2024 that deal with the insertion of the Physical Education professional in Public Health. Considerações Finais: considerando que a inserção do profissional de Educação Física estar vinculado a área da saúde, este profissional pode contribuir com as práticas corporais e atividades físicas como ação prioritária para a população brasileira e demandas do SUS.